Synthesis and characterization of flame retardant rigid polyurethane foam based on a reactive flame retardant containing phosphazene and cyclophosphonate - Yang, Rong; Wang, Bo; Han, Xiaofeng; Ma, Binbin; Li, Jinchun (Polymer degradation and stability, 2017)
A reactive flame retardant hexa-(5,5-dimethyl-1,3,2- dioxaphosphinane-hydroxyl-methyl-phenoxyl)-cyclotriphosphazene (HDPCP) was synthesized by using 5,5-dimethyl-1,3,2-dioxaphosphinane 2-oxide and hexa-(4-aldehyde-phenoxy)-cyclotriphosphazene via P-H addition reaction. And it was used to prepare flame retardant rigid polyurethane foams (FR-RPUFs). The effect of flame retardant HDPCP on physical-mechanical, thermal degradation and fire behavior properties of FR-RPUFs system has been investigated. The results suggested that HDPCP showed no obviously negative influence on physical-mechanical property of RPUF. The thermal stability and char residue at 700 °C of RPUF were enhanced by introducing HDPCP. HDPCP is benefit to improve flame retardance of RPUF. The limiting oxygen index (LOI) increased from 19 to 25% with incorporation of 25% HDPCP. Moreover, the peak heat release rate (PHRR), total heat release rate (THR), total smoke rate (TSR) and total smoke production (TSP) of RPUFs decreased due to a good char-forming ability of HDPCP.